Cholinergic REST-G9a gene repression through HMGB1-TLR4 neuroimmune signaling regulates basal forebrain cholinergic neuron phenotype - Crews, Fulton T.; Vetreno, Ryan P. (Frontiers in Molecular Neuroscience, 2022)
Lipopolysaccharide (LPS) and high-mobility group box 1 (HMGB1) are Toll-like receptor (TLR4) agonists that activate proinflammatory neuroimmune signaling linked to loss of basal forebrain cholinergic neurons (BFCNs) and cognitive deficits. Loss of choline acetyltransferase immunoreactive (ChAT + IR) BFCNs is generally interpreted as cell death, but recent in vivo studies find anti-inflammatory interventions restore adolescent ethanol exposure-induced persistent loss of adult ChAT + IR neurons and cognitive deficits, suggesting proinflammatory signaling-induced reversible gene repression of ChAT in BFCNs. Using an ex vivo Wistar rat basal forebrain slice culture (FSC) model to investigate TLR4 involvement in repression of the BFCN phenotype, we report that direct TLR4 activation with LPS decreases expression of multiple BFCN markers in the absence of observable neuronal loss or cell death. Inhibition of HMGB1 blunts while inhibition of TLR4 blocks the LPS-induced loss of ChAT + IR neurons. TLR4 activation induces the transcriptional repressor RE1-silencing transcription factor (REST) and the methyltransferase G9a while increasing repressive histone 3 lysine 9 dimethylation and REST occupancy at cholinergic gene promoters. G9a inhibitors both prevent and reverse the LPS-induced loss of ChAT + IR whereas siRNA inhibition of REST blocks the LPS-induced loss of ChAT + IR BFCNs. These data suggest in vivo HMGB1-TLR4 signaling in BFCNs leads to a reversible loss of the cholinergic neuron phenotype through epigenetic gene repressive mechanisms.